Effect of seed sett size on sprouting, shoot growth, and tuber yield of white guinea yam (Dioscorea rotundata) - Iseki, K.; Matsumoto, R. (Informa UK Limited, 2020)
Approximately 30% of harvested yams are used in subsequent plantings as seed tubers, which reduces the harvest size; however, planting tuber pieces (setts) potentially represents a viable alternative. To determine how sett size affects yam production, different sett sizes were compared for sprouting, shoot growth, and tuber yield. Larger setts exhibited faster sprouting with greater shoot biomass due to larger shoot growth rates during the early growth period. Tuber yield from 200 g setts was higher than that from 50 g setts; however, this yield advantage was not enough to compensate for the cost of larger sett size. Thus, planting 50 g setts might be the most cost-effective. Even the 50 g setts yielded higher than 1 kg tuber per plant which were available for selling in markets. Thus, planting with smaller setts can be promising method for efficiently improving yam production.